Effect of Storage Time and Temperature on Protein Content of White Anchovy (Stolephorus tri) - Aulia Azizah; Andi Suhendi (Jurnal Kefarmasian Indonesia, 2026)
Anchovy (Stolephorus tri) is widely consumed in Indonesia as a source of protein, but its nutritional quality is strongly influenced by storage conditions. This study aimed to quantify changes in soluble protein content (mg/mL) during storage at room temperature (25–32 °C), refrigeration (2–8 °C), and freezing (–20 °C) over 60 days. Fresh anchovy samples (n = 3 per time point, 5 g each) were analyzed using the Lowry method, and data were evaluated with repeated-measures ANOVA followed by Tukey’s post-hoc test (p<0.05). Results showed that protein content decreased significantly by 40.9% at –20 °C after 60 days (p<0.01), while refrigeration produced unstable fluctuations with a 74.9% increase at day 60 (p<0.05), and room temperature storage resulted in minor increases of up to 3.05%. Organoleptic evaluation indicated that freezer storage best preserved sensory quality compared to refrigeration and room temperature, although protein levels declined gradually. In conclusion, storage temperature and duration significantly affect protein content and sensory quality of anchovy, with freezing recommended as the most effective method to maintain quality during distribution, while confirmatory analyses such as SDS-PAGE, Bradford, or Kjeldahl are suggested to distinguish intact proteins from degradation products.